Buchering and curing meat on tfhe farm - Schroeder, William Paul (My University, 1906)
Introduction: The man cannot be counted a proficient farmer, if he cannot slaughter and handle his own meats. It is necessary for him to know the methods by which the different animals for meat are slaughtered. This qualification is necessary in order to have the best results in killing and handling meats for the farm. Selection of Animal. The quality of meat is influenced by several circumstances each of which produce a peculiar difference in the flesh of the same species of animals. The principal circumstances alluded to, are the breeds, the sex, the age, the nature of the food on which the animal has been fed, its state of health, and the treatment immediately previous to its being slaughtered. The first thing to consider in the selection of animals for meat is perfect health, at the time of its being slaughtered. No matter how good appearance the animal may have if the health is not good the best quality of meat cannot be obtained. Flesh from animals that have recovered from disease before slaughtering is not likely to cure well, and is also difficult to keep after curing. Bruises, broken limbs, or like accidents all have the same effect on meat as ill health. Unless the animal could be killed and dressed immediately should not be used for food, especially if there is a slight rise in temperature. The rise in temperature of the animal at the time of slaughtering, has a tendency to result in a poor quality of meet, and gives it a tendency to rapid putrification. Condition. An animal to produce good meat should have a reasonable amount of fat, as this adds juiciness and flavor to the meat. At the same time the fat should be evenly distributed over the carcass not occurring in patches or gobs. However the presence of large amounts of fat is not essential for wholesome meat.
Citation: Schroeder, William Paul. Buchering and curing meat on tfhe farm. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Meat Science; Butchering; Curing Meat; Farms; Theses